A Novel Diazomethane-Mediated Synthesis of Azetidine-Embedded Tetracyclic Ketal Systems - Rao, G. Hari Mangeswara (Synthesis, 2018)
Herein, the first diazomethane-mediated synthesis of azetidine-embedded tetracyclic ketal systems is reported. Reactions of norbornyl hemiaminal acetals with diazomethane afford azetidine-embedded tetracyclic ketals in good to excellent yields. The bridgehead-bromo-substituted hemiaminal acetals give higher yields compared to the corresponding bridgehead-chloro-substituted hemiaminal acetals. The hemiaminal acetals are prepared stereoselectively via nucleophilic addition of various amines to norbornyl α-diketones from the exo face.
Keywords: diazomethane; azetidines; amines; tetracyclic; acetals